What Makes an Effective Executive - Drucker, Peter F. (Boston Massachusetts : Harvard Business Review Press, 2017)
Since 1922,Harvard Business Review has been a leadung source of breackthroug ideas in management practice-many of which still speak to and influence us today. The HBR Classics series seminal pieces a part of your permanent management library. Each volume contains a groundbreaking idea that has shaped best practices and inspired countless managers around the world-and will change how you think about the business world today.
Tặng
Keywords: Business Managers; Managemet Pratice